The Effectiveness of Interval Training on Endurance Improvement in Adolescent Tennis Players - Azis, Ilham; Yusnadi, Yusnadi; Hasyim, Muhammad Qasash (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
Tennis is a sport that requires high endurance capacity, especially for adolescent athletes who are in their physical development phase. Interval training has been recognized as an effective method for improving cardiovascular endurance and sport-specific performance. This study aims to analyze the effectiveness of interval training in improving endurance in adolescent tennis players. This research employed a quasi-experimental design with a pretest-posttest control group approach. The study involved 40 adolescent tennis players aged 14-17 years, divided into two groups: an experimental group (n=20) receiving interval training and a control group (n=20) receiving conventional training. The intervention was conducted for 8 weeks with a training frequency of 3 times per week. Endurance was measured using the multistage fitness test (beep test) and tennis-specific endurance tests. The results showed significant improvement in endurance capacity in the experimental group compared to the control group (p<0.05). The experimental group showed an average increase of 18.5% in VO2max, while the control group only showed 7.2% improvement. Tennis-specific endurance tests also demonstrated superior results in the interval training group. Conclusion: Interval training proves to be more effective than conventional training methods in improving the endurance capacity of adolescent tennis players. This training method can be recommended as an optimal approach for developing cardiovascular fitness in young tennis athletes.